2015
DOI: 10.1371/journal.pgen.1005466
|View full text |Cite|
|
Sign up to set email alerts
|

Satellite DNA Modulates Gene Expression in the Beetle Tribolium castaneum after Heat Stress

Abstract: Non-coding repetitive DNAs have been proposed to perform a gene regulatory role, however for tandemly repeated satellite DNA no such role was defined until now. Here we provide the first evidence for a role of satellite DNA in the modulation of gene expression under specific environmental conditions. The major satellite DNA TCAST1 in the beetle Tribolium castaneum is preferentially located within pericentromeric heterochromatin but is also dispersed as single repeats or short arrays in the vicinity of protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 39 publications
3
85
0
1
Order By: Relevance
“…Low sequence variability of satDNA monomers has also been observed when their short segments are located in the proximity of genes. It was hypothesized that low sequence variability can in this case be a consequence of possible roles in gene regulation and/or chromatin structure [20, 21, 52]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low sequence variability of satDNA monomers has also been observed when their short segments are located in the proximity of genes. It was hypothesized that low sequence variability can in this case be a consequence of possible roles in gene regulation and/or chromatin structure [20, 21, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of sequence variability performed on the 1.688 satDNA of Drosophila [20] and on satDNAs of the beetle Tribolium castaneum [19] showed that satDNA copies located in euchromatic chromosomal domains evolve under similar rules as their counterparts in heterochromatic compartments. A heat-stress induced regulatory mechanism of transient genome-wide heterochromatinization has been recently proposed in T. castaneum as a possible functional role of isolated euchromatic satDNA copies [21]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In almost all eukaryotes, the DNA underlying centromeres is made of large tracts of nearly identical tandem DNA repeats, known as satellite DNA [13]. The remarkable variation of satellite DNAs between species has been an enigma ever since their discovery and different important roles have been ascribed to these sequences, from the imperative centromeric function in mitosis and meiosis to regulatory functions [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Finally, satDNA can influence gene expression, such as TCAST1 in the beetle Tribolium castaneum, which has been shown to suppress the expression of various proteincoding genes after heat shock (Feliciello et al 2015). SatDNAs performing a structural or functional role may contain various functional motifs, such as binding sites for centromeric proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%